Development of a simple and cost-effective gel-based duplex PCR method to identify both encapsulated and unencapsulated Neisseria meningitidis applicable under resource-limited conditions. Issue 5 (May 2021) - Takahashi, Hideyuki; Nakamura, Masaki; Matsumoto, Yuko; Yoshino, Shuji; Kakita, Tetsuya; Shimuta, Ken; Kamiya, Hajime; Saito, Ryoichi; Ohnishi, Makoto
Abstract: Tens of thousands of cases of invasive meningococcal diseases (IMD) with thousands of deaths are reported annually worldwide; however, only approximately 40 cases occur each year in Japan. Therefore, the majority of medical technologists in Japan have never performed or prepared for analyses of the causative agent, Neisseria meningitidis . Since IMD outbreaks have been reported at mass gathering events, the risk of IMD will increase in Japan in 2021 because of the Olympics. In the present study, we developed a new simple gel-based duplex PCR method that may be employed by the majority Japanese clinical laboratories. It is simple to perform and time- and cost-effectively identifies encapsulated and unencapsulated N. meningitidis by detecting the encapsulated N. meningitidis -specific ctrB and N. meningitidis -specific ggt genes. We consider this simple and cost-effective identification method to compensate for the lack of experience and resource-poor conditions in most Japanese laboratories in which N. meningitidis has rarely been examined.